The Influence of Work-Life Balance, Work Stress, and Work Environment on Employee Satisfaction at the Ima Shop Souvenir Center - Ningsih, Tuti Widiya; Paramitha, Dyah Ayu (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research objectives: This study aims to determine the Influence of Work-Life Balance, Work Stress, and Work Environment on Employee Job Satisfaction partially and simultaneously at the Ima Shop Souvenir Center. Design/Method/Approach: This study uses a quantitative method with an associative approach, the population is all permanent employees at the Ima Shop Souvenir Center, the number of samples is 30 respondents. The data analysis technique uses classical assumption test, multiple linear regression test, determination coefficient test, and hypothesis test with SPSS version 16 software. Research Findings: The findings of this study are that there is a positive and significant influence of the work-life balance variable on job satisfaction, and there is no positive influence of the work stress variable on job satisfaction, and there is no positive influence of the work environment variable on job satisfaction. And simultaneously the variables of work-life balance, work stress and work environment have a significant influence on job satisfaction. Theoretical contribution/originality: This research contributes to the human resources literature on Work-Life Balance, work stress, and work environment on job satisfaction. As well as helping MSMEs to understand the importance of creating a comfortable work environment, managing employee set-up, and supporting work-life balance to increase employee job satisfaction. Practitioner/Policy Implications: Providing policy recommendations to improve the balance between employees' work and personal lives, minimizing work stress and helping business owners to understand the importance of human resources in the success of a store. Research limitations: This study only focuses on employees who work at the Toko Ima Souvenir Center.